Sensory Ganglia-Specific TNF Expression Is Associated With Persistent Nociception After Resolution of Inflammation - Gonçalves, William Antonio; Rezende, Barbara Maximino; Oliveira, Marcos Paulo Esteves de; Ribeiro, Lucas Secchim; Fattori, Victor; Silva, Walison Nunes da; Prazeres, Pedro Henrique Dias Moura; Queiroz-Junior, Celso Martins; Santana, Karina Talita de Oliveira; Costa, Walyson Coelho; Beltrami, Vinícius Amorim; Costa, Vivian Vasconcelos; et al. (Frontiers in Immunology, 2020)
Joint pain is a distressing symptom experienced by arthritic patients and it is frequently persistent even after treatments that reduce signs of local inflammation. Continuous production of algogenic factors activate/sensitize nociceptors in the joint structures and contribute to persistent pain, a challenging and difficult condition to treat. TNF is a crucial cytokine for pathogenesis of several rheumatic diseases and its inhibition is a mainstay of the treatment for controlling joint symptoms, including pain. Here, we sought to investigate the inflammatory changes and the role of TNF in dorsal root ganglia (DRG) during persistent hypernociception after the resolution of joint inflammation in mice. Using a model of antigen-induced arthritis, the peak of joint inflammation occurred at 12-24 h after local antigen injection and was characterized by intense influx of neutrophils, pro-inflammatory cytokine production and joint damage. Inflammatory parameters in the joint returned to basal levels between 6 and 8 days after antigen-challenge, characterizing the resolving phase of joint inflammation. Mechanical hyperalgesia was persistent up to 14 days after joint insult. The persistent nociception was associated with inflammatory status of DRG after resolution of joint inflammation. The late state of neuroinflammation in the ipsilateral side was evidenced by gene expression of TNF, TNFR2, IL-6, IL-1β, CXCL2, COX2 and iNOS in lumbar DRG (L3-L5) and leukocyte adhesion in the lumbar intumescent vessels between the days 6 and 8. Moreover, there were signs of resident macrophages activation in DRG, as evidenced by increase in Iba1-positive cells. Intrathecal or systemic injection of etanercept, an agent clinically utilized for TNF neutralization, at day 7 post arthritis induction reverted the persistent joint hyperalgesia by specific action in DRG. Our results suggest that neuroinflammation in DRG after the resolution of joint inflammation drives the continuous neural sensitization resulting in persistent joint nociception in a mechanism mainly dependent on TNF.